Literature Review on 21st Century Learning Strategies: Roles, Challenges, and Future Directions - Mutmainah; Rosidah, Siti; Ilham, Muhammad (Ihsan Cahaya Pustaka, 2025)
The 21st-century education demands the development of critical, creative, communicative, and collaborative skills to prepare students for complex global challenges. This study aims to review 21st-century learning strategies, explore their roles, identify implementation challenges, and examine future trends and directions. A narrative literature review method was employed, synthesizing findings from peer-reviewed journals, academic publications, and policy documents related to 21st-century learning strategies. The results indicate that innovative models, including project-based learning, problem-based learning, gamification, blended learning, and collaborative learning, effectively enhance students’ motivation, engagement, problem-solving abilities, and creativity. Successful implementation depends on the integration of creativity, collaboration, and technology, supported by infrastructure, teacher digital literacy, and student-centered pedagogical design. Key challenges include limited digital infrastructure, teacher readiness, and the need for differentiated instruction. Implications highlight the importance of flexible curriculum design, supportive policies, and continuous professional development. Further research is recommended to develop AI-based adaptive media, open-source collaborative platforms, integration of socio-emotional learning, and multi-site evaluation to maximize the effectiveness of 21st-century learning strategies.